Penerapan Strategi Student Facilitator And Explaining Untuk Meningkatkan Keaktifan Belajar Dan Kemampuan Komunikasi Pada Pembelajaran IPA Siswa Kelas IV SDN Kwangen 1 Tahun 2015/2016 - Nurrohmah, Lintang Oen (2016)
The research aims to enhance the activity of learning and communication skills in learning science through the implementation of strategies Student Facilitator and Explaining. This type of research qualitative with other research design Measures (PTK). The subjects were students of class IV, totaling 19 students. Data were analyzed using interactive analysis consists of data reduction, data presentation, and conclusion. Based on the results obtained during the study of pre-cycle, the first cycle and the second cycle continues to increase. The results obtained from the indicators the activeness study: (1) active participation by asking the question 26, 32%, 47, 37% and 78, 95%, (2) active participation by answering question 21, 05%, 36, 85% and 76, 32%, (3) The active participation by discussing the lessons to his 31, 58%, 55, 25% and 89, 48%. While the indicator of the ability of communication: (1) Delivering material / results in class (presentations) 36, 84%, 50, 00% and 78, 95%, (2) Asking his opinion 26, 32%, 36, 85% and 76, 30%, (3) Commenting and provide feedback (refute) 21, 05%, 43, 11% and 76, 32%. The conclusion from this study that the implementation of the strategy Student Facilitator and Explaining able to enhance the activity of learning and communication skills in science teaching students of class IV SDN Kwangen 1 year 2015/2016.